Knowledge, Attitudes and Behaviours Towards Exclusive Breastfeeding Amongst Mothers in Sarawak, Malaysia: A Qualitative Study - Buss, Dr Imogen Margaret (IIUM Medical Journal Malaysia, 2019)
Introduction: Exclusive breastfeeding is recommended as the optimal method of infant feeding for the first six months, but the rate remains low in many countries, including Malaysia. It is important to understand barriers preventing exclusive breastfeeding, to enable tackling these issues and thereby improving maternal and child health. This study aims to do this by exploring the knowledge, attitudes and behaviours of mothers towards breastfeeding in Sarawak, Malaysia. Material and Methods: Qualitative methods were employed, using semi-structured interviews with an interpreter, conducted in Sarawak General Hospital between 16th April and 11th May 2012. Convenience sampling was used to recruit participants from the maternity wards. Interviews were conducted using a topic guide, were audio-recorded and transcribed verbatim. Analysis was based on conventional content analysis, with codes and themes developing from the interviews. Results: Analysis of the 17 interviews identified five major themes; (1) positive attitudes towards breastfeeding, (2) lack of knowledge relating to exclusive breastfeeding, (3) fear of insufficient milk, (4) methods to improve awareness and knowledge of breastfeeding, (5) improvements in the workplace. There is a lack of knowledge amongst mothers in Malaysia regarding breastfeeding, causing anxiety and early discontinuation of breastfeeding. Methods to improve education of mothers and healthcare staff have been suggested, as well as improvements to encourage breastfeeding in the workplace. Conclusion: Focused education for new mothers and widespread community education may help improve breastfeeding continuation rates. The provision of workplace facilities and flexible working hours for new mothers may help overcome physical barriers preventing breastfeeding continuation once back at work.